Clinical presentation of anti-N-methyl-d-aspartate receptor and anti-voltage-gated potassium channel complex antibodies in children: A series of 24 cases. (January 2018) - Konuskan, Bahadir; Yildirim, Mirac; Topaloglu, Haluk; Erol, Ilknur; Oztoprak, Ulkuhan; Tan, Huseyin; Gocmen, Rahsan; Anlar, Banu
Abstract: Objective: The symptomatology and paraclinical findings of antibody-mediated encephalitis, a relatively novel disorder, are still being characterized in adults and children. A high index of suspicion is needed in order to identify these cases among children presenting with various neurological symptoms. The aim of this study is to examine the clinical, demographic and laboratory findings and outcome of children with anti-NMDAR and anti-VGKC encephalitis for any typical or distinctive features. Methods: Cases diagnosed with anti-N-Methyld -aspartate receptor (NMDAR) and anti-voltage gated potassium channel (VGKC) antibody-mediated encephalopathy in four major child neurology centers are described. Results: In four years, 16 children with NMDAR and 8 children with VGKC antibody-associated disease were identified in the participating centers. The most frequent initial manifestation consisted of generalized seizures and cognitive symptoms in both groups. Movement abnormalities were frequent in anti-NMDAR patients and autonomic symptoms, in anti-VGKC patients. Cerebrospinal fluid (CSF) protein, cell count and IgG index were normal in 9/15 anti-NMDAR and 5/8 anti-VGKC patients tested. EEG and MRI findings were usually nonspecific and non-contributory. The rate and time of recovery was not related to age, sex, acute or subacute onset, antibody type, MRI, EEG or CSF results. Treatment within 3 months of onset was associated with normal neurological outcome. Conclusions: Our results suggest anti-NMDAR and VGKC encephalopathies mostly present with non-focal neurological symptoms longer than 3 weeks. In contrast with adult cases, routine CSF testing, MRI and EEG did not contribute to the diagnosis in this series. Highlights: Seizures were the most frequent initial symptoms in our anti-NMDAR group. The statistically significant difference in initial signs between anti-NMDAR and anti-VGKC groups is autonomic symptoms. Second-line immunotherapy was administered to 44% of children in anti-NMDAR group, 13% in VGKC group. The relapse rate was 6% in the NMDAR group. This study contributes to the recognition of ab-related encephalitis presenting with subacute cognitive symptoms in children.